Voluntarism as an investment in human, social and financial capital: Evidence from a farmer-to-farmer extension program in Kenya - Kiptot, Evelyne; Franzel, Steven (Springer, 2014)
A decline in public sector extension services in developing countries has led to an increasing emphasis on alternative extension approaches that are participatory, demand-driven, client-oriented, and farmer centered. One such approach is the volunteer farmer-trainer (VFT) approach, a form of farmer-to-farmer extension where VFTs host demonstration plots and share information on improved agricultural practices within their community. VFTs are trained by extension staff and they in turn train other farmers. A study was conducted to understand the rationale behind the decisions of smallholder farmers to volunteer their time and resources to train other farmers without pay and to continue volunteering. Data were gathered through focus group discussions and individual interviews involving 99 VFTs. Findings of the study showed that VFTs were motivated by a combination of personal and community interests that were influenced by religious beliefs, cultural norms, and social and economic incentives. Altruism, gaining knowledge and skills, and social benefits were the most frequently mentioned motivating factors for becoming VFTs.3 years after starting, the income earned from selling associated inputs and services was also a main motivating factor. There were no significant differences between motivating factors for men and women VFTs. The findings point to the fact that VFTs work effectively without being paid, but investments in human, social, and financial capital are crucial to keeping them motivated. These factors are key to ensuring the sustainability of farmer-to-farmer extension programs beyond the projects’ lifespan.